The protective effect of thymoquinone on tert-butylhydroquinone induced cytotoxicity in human umbilical vein endothelial cells - Karimi, Zahra (Royal Society of Chemistry, 2019)

(untitled) (Toxicol Res (Camb))
2-tert-Butyl-4-hydroquinone (TBHQ) is used for inhibition of oxidative rancidity in the food industry. However, this antioxidant can stimulate cytotoxicity in human umbilical vein endothelial cells (HUVECs). Thus, potential protective effects of thymoquinone (TQ) against TBHQ-induced cytotoxicity were investigated. Cytotoxicity was evaluated via MTT, flow cytometry, DAPI staining and DNA fragmentation methods. The obtained results revealed that treatment of HUVECs with TQ enhanced the cell viability rate and it had potential to reduce the cytotoxicity effect of TBHQ in cells. Also, in a combined regime of TQ and TBHQ, apoptosis was reduced compared to the cells treated with TBHQ (p < 0.05). Similarly, TQ had a protective effect on DNA and chromatin fragmentation of the cells treated with TBHQ. Finally, it can be concluded that TQ could be used as a protective agent against cytotoxicity induced by TBHQ in HUVECs.